ANALISIS PUTUSAN MAHKAMAH KONSTITUSI DALAM MENYELESAIKAN PERSELISIHAN HASIL PEMILUKADA DITINJAU DARI PERSPEKTIF TEORI HUKUM PROGRESIF (Kajian Terhadap Putusan MK atas sengketa hasil Pemilu Kepala Daerah Jawa Timur dan Putusan MK dalam Perkara Perselisiha - Maulidin, La Ode (Jurnal Konstitusi, 2011)
The Constitution Court, of which its duty is guard the 1945 Constitution of the Republic of Indonesia, has made a breaktrhough in the field of law. This Court is also intended to keep this government to run stably, and to make some corrections to the experiences of the country’s life in the past due to multiinterpretation to the constitution. In the 2003 Laws on rhe Constitution Court, it is stated that one of authorities of the Constitution Court is to settle the disputes on the results of general election. After the Court, according to the Law, is given authorities to settle the disputes, it has more authorities in the matter of Judicial Review to the Results of General Election. In the implementation, the Court has made many decisions on the Judicial Review to The Results of General Election in East Java and in South Kalimantan in accordance with the progressive law, where the Court has decided to make revoting and recounting in some areas. Among the experts, this is said to make some problems namely the Court has exceeded its authorities.